Ultrafine Bubbles Water priming to improve viability and vigor of bean (Phaseolus vulgaris) seeds - Nurfiana, Yuni; Suhartanto, M. Rahmad; Palupi, Endah Retno; Purwanto, Y. Aris (Journal of Tropical Crop Science, 2023)
Priming is a physiological technique of hydration of seed to improve metabolic processes before germination to accelerate germination and seedling growth under normal and stress conditions. This research is aimed to study the pretreatment using ultra-fine bubble (UFB) water to increase viability and vigor of seeds before planting (pre-planting) and during storage (pre-storage). This research was conducted at the Laboratory of Seed Quality Testing, IPB University, Indonesia. The research consisted of two experiments, i.e., UFB water priming to increase viability and vigor of bean seeds and its storability after priming. The first experiment was arranged using a completely randomized design with a combination of seed lot treatments (L1: initial germination percentage (GP) about 80%, L2: initial GP around 70%, and L3: initial GP around 60%) with priming (P0: no priming/control, P1: soaked in distilled water for 60 minutes, P2: distilled water for 120 minutes, P3: 8 ppm UFB water for 60 minutes, P4: 8 ppm UFB water for 120 minutes, P5: 20 ppm UFB water for 60 minutes, P6: UFB water 20 ppm for 120 minutes). The second experiment was arranged using a nested design with the main factor being the condition of the storage room and priming as the second factor nested in the main factor. The storage room condition factors consisted of KM: room conditions (temperature 28±5˚C, RH 73±7%) and AC: air-conditioned room (18±2 ̊C, RH 61±7%). The priming factor consisted of two levels, namely P0: without priming and P1: priming with 20 ppm UFB water soaked for 120 minutes. The results showed that priming treatment with UFB water 20 ppm for 120 minutes as a pre-planting treatment can increase the viability of bean seeds, particularly for seeds with low initial viability, and primed bean seeds with an initial viability of approximately 80% were able to retain their viability for 16 weeks of storage in an air-conditioned room.